Pathogenic Effects of Anti-Glycoprotein Ib Antibodies on Megakaryocytes and Platelets - Alimardani, Gulie; Guichard, Josette; Fichelson, Serge; Cramer, Elisabeth M. (Thrombosis and Haemostasis, 2002)
Antibodies directed against the glycoprotein (GP) Ib have been identified as the potential cause of various platelet disorders: Immune thrombocytopenic purpura (ITP) may be caused by such autoantibodies; Anti-thrombotic drugs targeting GPIb also induce thrombocytopenia. In order to elucidate the potential mechanism(s) of the anti-GPIb effects, we have examined by electron microscopy (EM) the effect of several antibodies directed against GPIb and GPIIb-IIIa on human culture megakaryocytes (MK). Virtually all antibodies to GPIb enhanced the interaction of newly formed platelets with MK when compared to other antibodies. These effects were retrieved when antibodies were tested on platelets. We conclude that antibodies to GPIb can potentially inhibit platelet release by MK, and can also induce homotypic platelet adhesion. These results may have implications in the pathophysiology of thrombocytopenia and platelet recovery in ITP, and shed light on the pathological effect of anti-GPIb antibodies used as antithrombotic drugs.
Keywords: Megakaryocytes; platelets; GPIb